Odpowiedzi

Najlepsza Odpowiedź!
2009-12-11T14:38:31+01:00
(-6) x [3 x (-5) + (-2) x (-5)] - 25
----------------------------------------------- + (-15) : 3 =
- 4 x 5 - (-3) x 7

(-6)x <(-15) + 10> -25
-------------------------------- + (-5) =
-20 +21

(-6)x (-5) -25
------------------ - 5 =
1
30-25
--------- - 5=
1
5
---- -5 =
1

5-5= 0
Kolejnosc dzialan
1. najpierw nawiasy
-mnozenie
dzilenie
dodawanie
odejmowanie

2009-12-11T14:39:18+01:00
-6×(-5)-25
------------ -5=5-5=0
-20 +21
2009-12-11T14:40:22+01:00
-6[3*(-5)+(-2)*(-5)]-25
--------------------------- + (-15)/3=
-4*5-(-3)*7

-6(-15+10)-25
= ------------------ -5=
-20-(-21)
(-6*-5)-20
= ----------------- -5=
-20+21
30-20
=------------ -5=
1

=10-5=5